Analisis Konsep Kebahagiaan dalam Pandangan Filsafat Islam - Setyariza, Nur Ayu; Kusumawardani, Intan; Widayati, Sri Erna; Handayani, Yekti; Kasori, Kasori (Lembaga Yasin AlSys, 2024)
Happiness is everyone's hope. Happiness is something that every human being dreams of. Humans in the Islamic view are creatures of Allah SWT, creatures created by Allah SWT. Islamic philosophy views that happiness can be achieved through rational thinking. Rational thinking is an effort to imitate God's actions. With the guidance of reason which is correlated with science, humans will be able to determine where they will depend for their happiness, namely only on Allah. The type of research used in this research is descriptive qualitative. This research aims to explain the phenomenon through data collection as in-depth as possible.